The impact of different time intervals between hCG priming and oocyte retrieval on ART outcomes - Ghasemian, Fatemeh (Research and Clinical Center for Infertility, 2013)
Background: Abnormal oocyte morphology has been associated with the hormonal environment to which the gametes are exposed. Objective: In this study, we evaluated the oocytes morphology, fertilization rate, embryos quality, and implantation rate resulted of retrieved oocytes in different times after human chorionic gonadotrophin (HCG) administration. Materials and Methods: A total of 985 metaphase II oocytes were retrieved 35, 36, 37 and 38 h after the injection of HCG as groups 1, 2, 3, and 4 respectively. Oocyte morphology was divided into (I) normal morphology, (II) extracytoplasmic abnormalities, (III) cytoplasmic abnormalities and (IV) intracytoplasmic vacuoles and in each group, oocytes were evaluated according to this classification. Results: Extracytoplasmic abnormalities were encountered in 17.76% and 31.1% of these oocytes (groups 3 and 4 respectively, p=0.007) in comparison with 12.23% group 2. Cytoplasmic abnormalities in group 4 were higher than other groups. 23.88% (p=0.039) and 43.25% (p=0.089) of resulted 2PN (two pronucleus) from groups 3 and 4 showed grade Z3 respectively in comparison to group 2 (16.44%). Normal and various categories of abnormal oocytes did not differ regarding fertilization and cleavage rates (p=0.061). However, group 4 showed significant difference in the rate of embryos fragmentation (grade III and IV embryo) in comparison with group 2 (40.96% vs. 24.93%, p=0.078). The pregnancy rate was higher in G2 and G3 groups (28.5 and 24.13% respectively). Conclusion: Oocyte retrieval time following HCG priming affected on oocyte morphology, 2PN pattern and embryos qualities subsequently. Both good quality embryo formation and pregnancy outcomes were noticeably higher when oocytes were retrieved 36 h after HCG priming in ART program.